Teaching learners with dysgraphia in primary schools in Embu - county, Kenya: implications for educational interventions - King’endo, Madrine; Njoki, Esther N. (My University, 2015)
The aim of this study was to identify challenges that teachers encounter in teaching Learners with Dysgraphia in primary schools in Embu County. This was to find out teachers’ competency in teaching learners with Dysgraphia, to establish academic related challenges caused by dysgraphia; to identify the assessment procedures for learners with Dysgraphia. The study was based on Maturational theory and the literature was reviewed under perspective of LD, characteristics of dysgraphia; instructional materials for learners with dysgraphia; effects of dysgraphia on academic performance of the learner and interventions for dysgraphia. The study adopted a descriptive survey design which was conducted in 4 primary schools from Manyatta Division in Embu County. The target population included the class teachers, the head teachers, learners with dysgraphia from the sampled schools and EARC Co-coordinator. The sample size included 4 head teachers, 4 class teachers, 1 EARC Co-coordinator and 220 pupils. Data was collected using questionnaires for the class teachers, observation schedule to learners identified with characteristics of dysgraphia and interview guide for head teacher and EARC Coordinator. A pre-testing of the research instruments was done to establish reliability and the validity. Quantitative data was analyzed using statistical package for social sciences (SPSS) while themes were organized for qualitative data. The results show that 75 percent of teachers lack instructional materials that cater for LD. Only 25 percent of teachers can identify cases of LD and give special attention. Lack of standardized tools for assessment at the EARC center may have led to poor identification and placement of LD. The researcher concluded that learning of the learners with dysgraphia is inadequate and this has been contributed by; lack of enough teachers trained in LD to identify learners with dysgraphia and apply appropriate teaching strategies, inadequate instructional materials that cater for LD and lack of standardized tools for assessment at the EARC center. The study recommends that the Ministry of Education should oversee special education training to all education officers and teachers. The EARC centers to be equipped with standardized tools for quality assessment of LD cases and teachers to be provided with instructional materials that cater for LD.
Keywords: Dysgraphia; Learning disability; Individualized Educational Program; Assessment and EARCH